KESALAHAN KALIMAT PADA PEMAKAIAN BAHASA PROPOSAL PENELITIAN MAHASISWA PBSI 2019 UNIVERSITAS AHMAD DAHLAN YOGYAKARTA - Zultiyanti Zultiyanti (Jurnal Nusantara Raya, 2022)
Student semester VII of the University PBSI Study Program Ahmad Dahlan class 2015/2016 experienced barriers in writing thesis proposal. A frequent obstacle is the error in the manufacture of sentences. Fenonema is quite interesting that the implementation of this study. The purpose of this study was for mendeskripikan the error in the use of sentences. The research proposal owned 46 student manuscripts belonging to the PBSI Study program in 2019 became a research subject. The research object is a sentence found on student research proposal semester VII Study program 2019. Data collection is carried out in an observation way. The data collected are then analyzed using a method at reference and distribusional method with technique for direct elements. Intra-rater and inter-rater were chosen to examine the validity of the data. The conclusion of the results of the analysis that the error of sentence usage only consists of the subject was only 96 sentences, sentences without the subject of 62 sentences. Mistake sentences without a subject and without predicated as many as 62 sentences. Sentence mistakes without predicated as many as 10 sentences. Meanwhile, errors in the subject use of the subject say in front as many as 16 sentences, the error in the use of the object said in front as many as 19 sentences. At the use of conjunction with a compound sentence, equivalent to conjunction with conjunction, while at the beginning of the sentence of 21 sentences, the use of conjunction and at the beginning of 9 sentences, the use of conjunction with conjunction and at the beginning of the sentence was 4 sentences, and the use of conjunction or at the beginning of the sentence. Furthermore, mistakes are found to use of conjunctions, if they have 13 sentences, conjunctions but 5 sentences, use for as many as 3 sentences, use of conjunctions, the use of conjunction with a number of sentences and use of conjunctions and serve as many as one sentence.